2020
DOI: 10.3390/cancers12082135
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Desmoid Tumor Therapy

Abstract: The desmoid tumor is a locally aggressive proliferative disease within the family of soft-tissue sarcomas. Despite its relatively good prognosis, the clinical management of desmoid tumors requires constant multidisciplinary evaluation due to its highly variable clinical behavior. Recently, active surveillance has being regarded as the appropriate strategy at diagnosis, as indolent persistence or spontaneous regressions are not uncommon. Here, we review the most recent advances in desmoid tumor therapy, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 77 publications
(101 reference statements)
0
17
0
1
Order By: Relevance
“…Traditional cytotoxic chemotherapies include doxorubicin/dacarbazine (ADIC), pegylated liposomal doxorubicin, and methotrexate (MTX) with vinca alkaloids, most commonly vinblastine. Newer therapies include tyrosine kinase inhibitors (TKI) such as imatinib, sorafenib, and pazopanib, and multiple novel treatments including gammasecretase inhibitors, Wnt/b-catenin inhibitors, and even immune checkpoint inhibitors are being studied in clinical trials (23). A few studies have examined the susceptibility of CTNNB1 mutation subtypes to various chemotherapies, with S45F mutations having worse outcomes with meloxicam, and no difference observed in different mutations in patients treated with MTX/vinblastine and imatinib (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional cytotoxic chemotherapies include doxorubicin/dacarbazine (ADIC), pegylated liposomal doxorubicin, and methotrexate (MTX) with vinca alkaloids, most commonly vinblastine. Newer therapies include tyrosine kinase inhibitors (TKI) such as imatinib, sorafenib, and pazopanib, and multiple novel treatments including gammasecretase inhibitors, Wnt/b-catenin inhibitors, and even immune checkpoint inhibitors are being studied in clinical trials (23). A few studies have examined the susceptibility of CTNNB1 mutation subtypes to various chemotherapies, with S45F mutations having worse outcomes with meloxicam, and no difference observed in different mutations in patients treated with MTX/vinblastine and imatinib (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…MUC4 has also been reported as a highly sensitive and specific marker for low-grade fibromyxoid sarcoma [ 18 ]. Besides Wnt/β-catenin signaling, the Notch pathway has also been reported as a potential therapeutic approach for desmoid tumors [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism(s) by which tyrosine kinase inhibitors (TKIs) act in DT has not been fully elucidated, 70 overexpression of platelet-derived growth factor receptor β (PDGFRβ), which is inhibited by the TKI imatinib, has been postulated to drive DT development and growth. 71 Initial case reports suggested that imatinib had efficacy in patients with DT. 72 Subsequently, multiple prospective trials evaluated the safety and efficacy of TKIs in patients with DT (Table 1).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%